A critical realist study into the emergence and absence of academic success among Bachelor of Emergency Medical Care students - Sobuwa, Simpiwe (Division of Emergency Medicine, 2019)
This critical realist thesis explores academic success in the four-year Bachelor of Emergency Medical Care degree in South Africa. The Bachelor of Emergency Medical Care degree is a relatively new degree that is offered at four universities in South Africa. In view of the existing shortage of paramedics both in South Africa and on the African continent, an understanding of the factors that play a role in academic success may lead to an increase in the number of emergency care providers. Accordingly, this study was conceptualised to explore the reasons why academic success is either evident or absent among Bachelor of Emergency Medical Care students. The study utilised a sequential, explanatory, mixed methods research design. The quantitative phase consisted of an online survey that was disseminated to Bachelor of Emergency Medical Care students in South Africa with the aim of gaining an insight into their socio-cultural history. Continuous and categorical variables were described using basic descriptive statistics. The Pearson’s chi-square and Fisher’s exact test were used to test associations between the various survey variables and repeating a year. A p-value of less than 0.05 was considered to be statistically significant. During the qualitative phase focus groups were held with students while semi-structured interviews were conducted with lecturing staff members. The aim of the qualitative approach was to explore the causal powers and generative mechanisms that give rise to or enable the emergence or absence of academic success among Bachelor of Emergency Medical Care students. Thematic analysis was used to analyse results from the focus groups and semistructured interviews. A critical realist concept of the laminated system was also used to explore the themes that emerged. A total of 176 participants from an available sample of 408 students responded to the survey. Not repeating a year was significantly associated with two important variables, namely, the possession of a pre-existing emergency care qualification and not being a white student. The results revealed that the following interactive generative mechanisms played a role in the lack of academic success, namely, biological, socioeconomic, socio-cultural, normative, psychosocial and psychological factors while the following interactive generative mechanisms facilitated the emergence of academic success – psychological, psycho-social, normative and socioeconomic factors.